GERAKAN KESALEHAN KELOMPOK SUFI SAR JUBA RESCUE TAREKAT SYADZILIYYAH DI SURAKARTA - Warsito Warsito; Muhammad Zainuddin (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2023)
This reseach studies the conversion of the identity of a group of ex hoodlums into the SAR group of Juba Rescue of the Syadziliyyah Tarekat. The group of ex hoodlums of Juba Rescue of Syadziliyyah tarekat is a new phenomenon that finds ascetic Sufi teachings with a hoodlums past experiments that is far from worship values and hunts the world at all costs. They try to get closer to Allah with various Islamic practices such as dhikr, visiting graves, and reading the Qur'an, at the same time they also entertain themselves by playing music, singing, playing chess, smoking and staying up late. This group was fostered by K.H. Muhammad Ali, one of the sons of K.H. Naharsurur, founder of the Ta'mirul Islam boarding school. This new phenomenon is studied using a qualitative method with a phenomenological approach. Meanwhile, the theory used in this study is the theory of social identity and social movement. These two theories explain the social conditions that enabled the emergence of this group, explain the framing process or the process of coaching ex-hoodlums and explain the process of mass mobilization. In the study, it was found that the past street life of ex hoodlums had an effect on the process of learning religion and the spirit of carrying out their religious life. Religious activities that combine Sufi piety and worldly pleasures become a religious pattern that can bridge the da'wah of Islam to street people.